Isobolographic analysis of analgesic interactions of silymarin with ketamine in mice - NASER, A.S.; ALBADRANY, Y.; SHAABAN, K.A. (Journal of the Hellenic Veterinary Medical Society, 2020)
The present study was undertaken to explore the analgesic effect of silymarin and ketamine alone or in combination in mice. Analgesia was measured by using a hot plate and the writhing test. The up-and-down method was used to determine the median effective analgesic dosages (ED50s) of silymarin and ketamine administered intraperitoneally (ip) either alone or together. The ED50s of both drugs were analyzed isobolographically to determine the type of pharmacological interaction between them. The analgesic ED50s for silymarin and ketamine in mice were 57.22 and 1.96 mg/kg, ip, respectively. Concomitant administration of the silymarin and ketamine at fixed ration (0.5:0.5) of their individual ED50s was 38.4 mg/kg and 1.28 mg/kg, ip, respectively. Silymarin and ketamine at fixed ration (1:1) of their individual ED50s were 47.54 mg/kg and 1.58 mg/kg, ip, respectively . Depending on the isobolographic analysis and calculating Y value, the type of pharmacological interaction between silymarin and ketamine at a ratio of 0.5:0.5 and 1:1 of their analgesic ED50 values of each drug , was antagonistic .In the writhing test the concomitant administration of silymarin and ketamine at 120mg/kg and 4mg/kg , ip, respectively reduce significantly the numbers of writhing in compare with silymarin120 mg/kg,ip and ketamine 4mg/kg, ip separately. The results suggest that the co-administration of silymarin and ketamine was ineffective to reduce the central pain while the concomitant administration of silymarin and ketamine was effective to reduce the visceral pain.